calculus
posted by Riley on .
I need help simplifying this problem.
f(x)=x^4/5(x4)^2
f'(x)=x^4/5*2(x4)+(x4)^2*4/5x^1/5
it is suposed to end up as this:
1/5x^1/5(x4)[5*x*2+(x4)*4]
but how do i get it to there? I need to see all the steps and how to get them. Thanks

your first line is good
now, do you notice x^(1/5) and x^(4/5) ?
isn't x^(1.5) the highest common factor ? (just like a^4 would be the HCF for a^4 and a^6)
also (x4) is a common factor,
as well as 1/5 (pretend your first term was (5/5)x^4/5*2(x4)
so
(1/5)(x^(1/5)(x4)[10 + 4(x4)]
= (1/5)(x^(1/5)(x4)[4x6]
= (2/5)(x^(1/5)(x4)[2x3] 
prove that sin invers (1/5)+COT INVERSE (3)=0